Kajian pengembangan agrotechnopreneurship berbasis potensi sektor pertanian di Kabupaten Jember - Yuli Wibowo; Herlina Herlina; Siswoyo Soekarno; Andi Eko Wiyono; Eva Yulia Windiari; Ajeng Afriska Lailatul Fajriyah (AGROINTEK, 2024)
Jember Regency is an agricultural area in East Java Province that produces various agricultural commodities that can be used as a base in developing agrotechnopreneurship activities. In general, this research aims to analyze the potential for agrotechnopreneurship development based on the potential of the agricultural sector in Jember Regency, including subsectors of food crops, horticulture, plantations, fisheries, and livestock. The aspects studied in detail include identifying agrotechnopreneurship products that have the potential to be developed in Jember Regency, determining potential agrotechnopreneurship products in each agricultural subsector, calculating the added value obtained, and estimating market opportunities for potential agrotechnopreneurship products. There are several methods used in this research, including descriptive methods for the identification of agrotechnopreneurship products, the MPE method to determine potential agrotechnopreneurship products, the Hayami method to calculate the added value of potential agrotechnopreneurship products, and Least Square method to calculate the estimated amount of market demand for potential agrotechnopreneurship products. The results showed that the number of agrotechnopreneurship products identified was recorded at 93 products, including products from the food crop subsector (23 products), horticulture subsector (28 products), plantation subsector (17 products), livestock subsector (5 products), and fishery subsector (20 products). Agrotechnopreneurship products selected as potential products include mocaf flour (food crops), chili sauce (horticulture), coconut briquettes (plantation), cow's milk kefir (livestock), and shredded catfish (fishery). Agrotechnopreneurship products that have the highest added value are coconut briquettes (49%) and shredded catfish (45%), followed by cow's milk kefir (39%), mocaf (18%), and chili sauce (10%). The results of the market potential analysis show that the potential agrotechnopreneurship products analyzed have good market prospects and tend to increase market demand.